As transformações da paisagem urbana ao longo do Rio Poxim em Aracaju-SE - Santos, Weslainy Lemos (2021)
The morphology of the urban landscape influences the social, cultural and environmental daily life of the urban space, directly reflecting on the relationship between the citizen and the lived space. The quality of the urban environment directly depends on the environmental issues related to this space and how they are understood and treated as resources in the natural resources within the city. Thus, this study aims to analyze the transformations of the urban landscape along the Poxim River in the city of Aracaju, from 2003 to 2020, with a focus on urban morphology, through the built-up space on the banks of the river. For that, a qualitative and quantitative descriptive research was carried out, formulated through a theoretical foundation with the study of the relations between the concepts of landscape, sustainability and development, passing through the current environmental and urban legislation, with a focus on urban rivers. Field research was carried out, with observation of the landscape and photographic survey throughout the course of the river in the city, in addition to analysis of data collected from public agencies and analysis of satellite images of the studied area. From the data obtained and the mapping of the transformations, it was possible to verify how the landscape was transformed on the banks of the Poxim and as a result the urban landscape along the river. The research made it possible to better understand the relationship between landscape and urban rivers, as well as to identify that the production of the urban landscape along the Poxim River is hostage to the interference of real estate speculation, generating concentration points in certain places of greater financial interest, especially after the insertion of infrastructure by the State. The landscape along the Poxim River is diverse, changing urban morphology with buildings of similar architectural typologies and templates, with emphasis on vertical condominiums. The research also highlighted the need for a closer look at urban planning with regard to architectural constructions along urban rivers.